PROBLEMS OF ECONOMIC ACTIVITY AT HIGH RISK FACILITIES: LEGAL SECURITY REGIMES - Bezzubov, Dmytro; Gavva, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is a comprehensive legal analysis of the existing system of means of state regulation of economic activity at high risk, to determine the extent of the impact of institutional levers on the protection of economic activity. Research methods: in the course of work the basic scientific methods of the system analysis, formal logic and a method of classifications are used. The method of systematic analysis is used accordingly to determine the current state of legislation in the field of ensuring the activities of high-risk entities. The method of formal logic allowed to determine scientific views on the categories of legal regimes in the field of law. The method of classifications allowed to identify ways to further improve the institutional methods of influencing legal regimes. Results: the study of legal regimes allows to identify ways and methods to minimize the impact of negative factors and risks of the economic environment on the state. The results of the study presented in this scientific article allow us to identify further steps in the study of the problems of legal regimes of economic activity. Discussion: the problems of legal regimes are applied from the standpoint of the development of the law of the modern state. The problem of economic activity at high risk is part of the economic sphere of public safety. The economic sphere of ensuring the public security of Ukraine as a system of fundamental, typical properties of any country embodies all spheres of life and development of man, society, state and nation. In general, in this aspect, security can be defined as a qualitative characteristic of the object (system), the ability of the object to exist, develop and protect it from internal and external threats. The place, role and priority of each element of the economic security sphere is determined by the circumstances that actually develop over a period of time inside and outside the facility. As the situation changes, its various properties may become vital. From the point of view of the national economy, the economic security of society is its state, which ensures the protection of national interests, resilience to internal and external threats, the ability to develop and protect the vital interests of society, nation and state. Vital interests in this context are understood as a set of needs that ensure the existence and progressive development of society as a whole. An adequate level of economic security is achieved through the implementation of a unified state policy, which must be supported by a system of coordinated measures adequate to internal and external threats. Without such a policy it is impossible to overcome the crisis, to force the mechanism of economic management, to create effective mechanisms of social protection. The activities of economic entities as objects of increased danger are part of the regulation of economic activities of individuals and legal entities. At present, Ukraine has formed an array of laws and bylaws in the field of administrative and legal support of public safety of Ukraine, which has a certain structure and requires systematization. The administrative and legal regime for ensuring the activities of high-risk entities is a set of measures of information and psychological influence on the behavior of individuals and legal entities, public authorities and local governments, which determine the procedure for monitoring, forecasting and neutralizing threats of various origins. in all spheres of public life related to the administrative authorization of the activities of individuals and legal entities for the legal use and designation of man-made and natural sources of danger that could potentially pose a threat of harm to public safety facilities.